The Correlation between The Knowledge Level of Diabetes Management toward The Preprandial Glucose Levels - Haris, Fahni; Kristianti, Linda Yuli (Universitas Muhammadiyah Yogyakarta, 2020)
Background: Knowledge about diabetes mellitus affects the lifestyle of patients who suffer from diabetes mellitus. Knowledge is one of the essential factors that determine health management for patients.Objective: This study aimed to determine the relationship between the knowledge level of diabetes mellitus (DM) management and preprandial glucose levels.Method: This study uses a quantitative cross-sectional method in which the correlation between the knowledge level and the preprandial glucose levels was calculated.Â Sixty-eight respondents were selected using purposive sampling. The knowledge level of DM management was measured using a questionnaire which consists of 28 questions. The value of the preprandial glucose level was measured using a test tool (easytouchÂ®). The data were analyzed using Pearson product-moment correlation test. The study was conducted from January to February 2019.Result: The result shows that respondents have a high level of knowledge of diabetes management, in which the score is 20.37 on average. The respondents have an average preprandial glucose level of 139.72 dl/mg. The Pearson product-moment correlation test shows a significant correlation between the knowledge of DM management and the preprandial glucose level with the coefficient correlation at -0.422, and p0.001 (Ï0.05).Conclusion: There is a correlation between the knowledge level of diabetes management toward preprandial glucose levels.